The effect of benralizumab on inflammation in severe asthma: a real-life analysis - Dina Visca; Francesco Ardesi; Martina Zappa; Sarah Grossi; Patrizia Pignatti; Marco Vanetti; Laura Pini; Giovanni Sotgiu; Rosella Centis; Giovanni Battista Migliori; Antonio Spanevello (Therapeutic Advances in Respiratory Disease)
Background: Benralizumab is a monoclonal antibody treatment for severe eosinophilic asthma (SEA). Few studies investigated its role in airway inflammation and its correlation with lung function. Objectives: The aim of the present study is to assess its effect after 1 year of treatment, focusing on airway inflammation. Design: This is a retrospective observational study, in an Italian tertiary reference centre specialised in diagnosis and management of severe asthma patients. Methods: We conducted a monocentric retrospective study including SEA patients treated with benralizumab for 1 year. Clinical, functional and inflammatory data were collected at baseline, 6 (T6) and 12 (T12) months. Results: Twenty-two SEA patients on benralizumab were included. We observed a reduction in exacerbations rate and systemic steroid treatment ( p  < 0.0001) as well as an improvement in asthma control ( p  < 0.0001), health-related quality of life ( p  = 0.017) and lung function pre-BD FEV1 (L) ( p  = 0.02) and percentage ( p  = 0.004) and post-BD FEV1 (L) ( p  = 0.01) and percentage ( p  = 0.003) from baseline to T6 and T12. A reduction in sputum eosinophil percentage was observed at T6 and T12 ( p  < 0.005). We found a positive correlation between the variation of sputum eosinophils percentage and FEV1 (L) at T12 (rho = −0.79, p  = 0.04). Moreover, the improvement of FEF 25%–75% from baseline to 6 (rho = −0.53, p  = 0.03) and 12 (rho = −0.62, p  = 0.01) months negatively correlated with the duration of asthma disease. In our cohort 12/22 patients were super-responders at T6 and 15/22 at T12. Furthermore, clinical remission was reached by 12/22, and all of them obtained blood and sputum eosinophils counts normalisation. Conclusion: Our data confirm that it is a rapid and effective treatment for SEA acting on clinical, functional, systemic and airway inflammatory outcomes. Our results highlight the role of induced sputum as a promising non-invasive technique to investigate pathophysiologic mechanisms in severe asthma treated with biologics. Finally, a negative correlation between small airway improvement and the duration of asthma may suggest that a prompt referral to asthma centres may delay lung function worsening. Additional studies are needed to investigate more in-depth the role of induced sputum in the management of asthma, response to treatment and remission.